The relationship between physical activity and academic performance on elementary school students - Komarudin Komarudin; José V García-Jiménez; Saryono Saryono; Ranintya Meikahani; Ari Iswanto; Satya Perdana; Galih Pamungkas (Jurnal Cakrawala Pendidikan, 2023)
While physical activity can be one of the daily supports for good health that can help the educational process, the present study aims to determine the relationship between physical activity and academic achievement. It was quantitative correlational research involving 1045 students from 21 elementary schools (ESs) selected through proportional random sampling. Physical activity was measured by using the Assessment of Physical Activity Levels Questionnaire (APALQ), and academic achievement was investigated through the average scores of the previous semester's report card. The study revealed three categories of physical activity, namely ‘very active’, ‘moderately active’, and ‘inactive’. Less than 30 ES students (3%) were reported ‘very active’, 460 students (44%) were ‘moderately active’, and more than half (53%) were ‘inactive’. With a percentage of 33%, the overall average result of physical activity gained was 348, meaning that the average increase fell within the moderate range. While having a sig. value greater than 0.05 (0.529), the study suggests that there is no significant correlation between physical activity and academic performance. The study's weak correlation coefficient of 0.020 involves drawing the inference that there is no discernable relationship between physical activity and academic achievement on elementary school students.